Are rural regions prioritizing knowledge transfer and innovation? Evidence from Rural Development Policy expenditure across the EU space. (July 2017) - Bonfiglio, A.; Camaioni, B.; Coderoni, S.; Esposti, R.; Pagliacci, F.; Sotte, F.
Abstract: Knowledge transfer and innovation (KT&I) are vital for sustainable rural development. European Rural Development Policy (RDP) has a long tradition of stimulating innovation in the rural space. In particular, in the 2007–2013 programming period, some measures have been explicitly targeted to support KT&I in agriculture and in rural economies. This paper aims to analyse the spatial distribution of the actual expenditure for measures promoting KT&I across the EU over the 2007–2011 period. In order to describe the main differences affecting the territorial allocation of this support, differences at rural development programming level are firstly taken into account. Then, the paper assesses "local" differences, i.e. those concerning the expenditure intensity at the NUTS 3 level. Findings point to an uneven and sometime low uptake of available opportunities. Imbalances come from both top-down political decisions and bottom-up capacity to attract and spend EU funds. In contrast with RDP objectives, the remotest and the most agricultural EU regions tend to show a lower expenditure intensity for KT&I measures. Highlights: Knowledge transfer and innovation (KT&I) are essential for sustainable rural development. EU Rural Development Policy (RDP) is having a major role in stimulating innovation in the EU rural space. The territorial allocation of RDP real data expenditure at a high territorial disaggregation (NUTS 3 level) is analysed. Most expenditure under KT&I measures currently targets urban or intermediate regions. The remotest and the most agricultural EU regions tend to receive a relatively lower KT&I expenditure.